(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تمّ تحديد كمية دقائق الغبار الصلبة المترسبة على أوراق بعض الأشجار المنتشرة على امتداد الساحل السوري وتراكيز بعض العناصر المعدنية الثقيلة فيها (Zn, Fe, Pb, Cu, Ni, Cd, Co, Mn), حيث تمّ انتقاء مواقع قريبة من مراكز النشاطات الصناعية وأخرى قريبة من قطاعات النشاط البشري الزراعي , ومواقع بعيدة نسبياً عن مصادر التلوث. أظهرت النتائج أن كمية دقائق الغبار الصلبة المترسبة على أوراق الأشجار وتراكيز بعض العناصر الثقيلة مثل الكوبالت Co, الكادميوم Cd , النيكل Ni, والرصاص Pb فيها تزداد بالقرب من المواقع الصناعية والحركة المرورية الكثيفة لتنخفض في المواقع البعيدة نسبياً عن مصادر التلوث المباشر, كما أن أشجار السرو تحتجز كميات أكبر من دقائق الغبار الصلبة , لتأتي بعدها أشجار الازدرخت والكينا والأكاسيا والدفلة وأخيرا النخيل. This study deals with the determination of the quantity of solid dust particles deposed on the leafs of some trees along Syrian coast and the concentration of some heavy metals in it (Zn, Fe, Pb, Cu, Ni, Cd, Co, Mn) .Some sites near to human and industrials activities , and others near to agriculture activities , and others relatively far from pollution sources has been selected. The results showed that the quantity of solid dust particles on leafs trees and concentration of heavy metals in it such as (Pb, Ni, Cd, Co) increasing near the industrials activities and dense traffic, and decreasing in the sites that relatively far from of pollution sources. However Cypress trees attach solid quantities more than Pride of china, following Rever red gum and Blue-leafed wattle and Oleander, and the Palm tree come in the last.